3-Hydroxy-1-methyl-2-[4-(piperidin-1-yl)phenyl]quinolin-4(1H)-one - Wera, Michał (International Union of Crystallography, 2011)
There are two structurally similar but crystallographically independent molecules (A and B) in the asymmetric unit of the title compound, C(21)H(22)N(2)O(2), which are linked via two O—H⋯O hydrogen bonds. An intramolecular O—H⋯O hydrogen bond also occurs in each molecule. In the crystal, the A and B molecules are further linked through C—H⋯O interactions. The benzene ring is twisted at an angle of 69.9 (1) and 83.4 (1)° relative to the 1,4-dihydroquinoline skeleton in molecules A and B, respectively. Adjacent 1,4-dihydroquinoline units of molecules A are parallel, while molecules A and B are oriented at an angle of 32.8 (1)°.